Large Energy Capacitive High-Entropy Lead-Free Ferroelectrics - Chen, Liang; Yu, Huifen; Wu, Jie; Deng, Shiqing; Liu, Hui; Zhu, Lifeng; Qi, He; Chen, Jun (Nano-Micro Letters, 2023)
Advanced lead-free energy storage ceramics play an indispensable role in next-generation pulse power capacitors market. Here, an ultrahigh energy storage density of ~ 13.8 J cm−3 and a large efficiency of ~ 82.4% are achieved in high-entropy lead-free relaxor ferroelectrics by increasing configuration entropy, named high-entropy strategy, realizing nearly ten times growth of energy storage density compared with low-entropy material. Evolution of energy storage performance and domain structure with increasing configuration entropy is systematically revealed for the first time. The achievement of excellent energy storage properties should be attributed to the enhanced random field, decreased nanodomain size, strong multiple local distortions, and improved breakdown field. Furthermore, the excellent frequency and fatigue stability as well as charge/discharge properties with superior thermal stability are also realized. The significantly enhanced comprehensive energy storage performance by increasing configuration entropy demonstrates that high entropy is an effective but convenient strategy to design new high-performance dielectrics, promoting the development of advanced capacitors Highlights: 1 Ultrahigh energy storage density of ~ 13.8 J cm−3 and large efficiency of ~ 82.4% are achieved in high-entropy lead-free relaxor ferroelectrics via high-entropy strategy, realizing nearly ten times growth. 2 Outstanding energy storage properties are attributed to the enhanced random field and breakdown field, decreased nanodomain sizes, strong multiple local distortions coexisting in-phase and anti-phase oxygen octahedron tilts. 3 Evolution of energy storage performance and domain structure with the increase in configuration entropy is systematically revealed for the first time.